Comparison of the New Type Modular Panel for Green Roofs and Classical Construction of Green Roofs by Stormwater Management. Issue 2 (November 2021) - Hejl, Martin; Mohapl, M.; Bříza, Lukas
Abstract: Proper stormwater management is one of the main problems cities today face. In order to understand how to properly manage urban stormwater it is first necessary to construct roofs with new construction methods. The first step for controlling urban stormwater is the construction of green roofs. We already know that the construction of green roofs improves water management in cities. But can we make it better? What will happen if we use the same layers for the green roofs but with a different construction method? This article wants to answer these questions. In this article the two green roofs, differing in the construction method, are compared and contrasted in terms of stormwater management. One of the green roofs was built traditionally, while the other has been built using a new type of modular panel. The article then compares their results during laboratory tests. In the conclusion you can read about measured data from tests and possible solutions and development of solutions to improve green roofs in the future.